PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP ATTITUDE TOWARD USING SIA KSB DENGANTECHNOLOGY ACCEPTANCE MODEL - Sigit Birowo; Hanes Riyadi (Jurnal Informatika dan Bisnis, 2014)
Information systems that change over time and the fast-paced online education has been sweeping the world, so more and more outstanding information and complexities. Academic information system is a tool to consolidate between the needs of learning process and an important means and support for effective learning in universities. Infrastructure renewal process from conventional towards more modern was implemented at KSB (Kwik Kian Gie School of Business) started in 2004. This study discusses what factors are interrelated and affect the level of technology acceptance of SIA (academic information system) at KSB by it’s lectures, students and supporting staffs with TAM (Technology Acceptance Model). This study was aimed to show up the roles Perceived Ease Of Use and Perceived Usefulness play in shaping Attitude Toward Using SIA KSB. All of the hypotheses were empirically supported and this meant the Perceived Ease Of Use and Perceived Usefulness jointly contributed positively the Attitude Toward Using SIA KSB.